MENGGAGAS PENDIDlKAN BERBASIS PLURALISME - Agustinus Pratisto Trinarso (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2013)
The idea of education based on pluralism leads the students to have good character, a positive attitude and to respect what may be different from what they personally hold. In itself, there is indeed a difference. In the face of such a difference, our attitude should be that of understanding, acceptance and to do what is fair on the basis of proportionate justice. On the other hand, discrimination is to do an injustice towards an individual or a group in society just because that individual or group is different in se. There is also a difference that comes from a specific personal attitude or conviction. This difference is related to differing outlooks and ways of life that are embraced and lived by someone. When it comes to difference in conviction and the choice of religion, a person should learn how to live together in mutual tolerance, developing a sense of respect before such differences. In the face of such differences, a man may debate and present opposing arguments. Openness and room for discussion and dialogue should precisely be fostered when there are differences like this. Differences in mental frameworks and thought should be analysed in an atmosphere of freedom to hold an opinion, dialogue and communicate in a healthy way. An education based on pluralism teaches the student to develop a character that is wise, promotes the skill to manage differences and designs a strategy that would resolve these differences in a mature way.